Metabolic perturbation sensitizes human breast cancer to NK cell-mediated cytotoxicity by increasing the expression of MHC class I chain-related A/B - Fu, Dexue (Oncoimmunology, 2015)
Cleavage or shedding of the surface antigen, MHC class I chain-related (MIC) protein (A/B) has been known to be one of the mechanisms by which tumor cells escape host immune surveillance. Thus, any strategy to augment the surface expression of MICA/B could facilitate anticancer immune response. Here, we demonstrate that metabolic perturbation by the glycolytic inhibitor, 3-bromopyruvate (3-BrPA) augments the surface expression of MICA/B in human breast cancer cell lines, MDA-MB-231 and T47D. Data from in vitro studies show that a non-toxic, low-dose of 3-BrPA is sufficient to perturb energy metabolism, as evident by the activation of p-AMPK, p-AKT and p-PI3K. Further, 3-BrPA-treatment also elevated the levels of MICA/B in human breast cancer cell lines. Significantly, 3-BrPA-dependent increase in MICA/B levels also enhanced the sensitivity of cancer cells to natural killer (NK-92MI)-mediated cytotoxicity. In vivo, 3-BrPA-pretreated cells demonstrated greater sensitivity to NK-92MI therapy than their respective controls. The antitumor effect was confirmed by a reduction in tumor size and decreased tumor viability as observed by bioluminescence imaging. Histological examination and TUNEL staining demonstrated that NK-92MI administration promoted apoptosis in 3-BrPA-pretreated cells. Taken together, our data show that targeting energy metabolism could be a novel strategy to enhance the effectiveness of anticancer immunotherapeutics.